Bundled Solutions of Index Insurance with Climate Information and Seed Systems to manage Agricultural Risks (BICSA). - Amarnath, Giriraj (CGIAR Research Program on Water, Land and Ecosystems, 2019)
The anomaly index uses daily Soil Water Index to quantify the moisture condition at various depths in the soil. It is mainly driven by precipitation via the process of infiltration. The data is available at 10km resolution, based on SSM (Surface Soil Moisture) observations from MetOp-ASCAT satellite data provided by Copernicus Global Land Service.